AKUNTABILITAS SISTEM E-PROCUREMENT DALAM PENGADAAN BARANG DAN JASA SEKOLAH MELALUI SISTEM INFORMASI PENGADAAN SEKOLAH (SIPLAH) (STUDI KASUS : SD SARASWATI 5 DENPASAR) (CITIZEN CHARTER, 2022)
This study aims to determine the extent of the accountability of the e-procurement system in the procurement of school goods and services through the School Procurement Information System (SIPLah) at Saraswati 5 Elementary School Denpasar. The author uses qualitative research methods whose studies are reviewed from written regulations. The author uses the basic legal reference in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 14 of 2020 concerning Guidelines for the Procurement of Goods/Services by educational units. The author also uses the theoretical reference from Koppel (2005) in measuring accountability including 5 dimensions including transparency, accountability, control, responsibility, and responsiveness. The results findings show of the dimensions of accountability which include transparency, accountability, control, responsibility, responsiveness show that SD Saraswati 5 Denpasar leads to an optimal level of accountability and principles in the procurement of goods and services by education units. Keywords: Accountability, Procurement of Goods and Services, SIPLah